2021
DOI: 10.1016/j.xcrm.2021.100241
|View full text |Cite
|
Sign up to set email alerts
|

Knee orthopedics as a template for the temporomandibular joint

Abstract: Although the knee joint and temporomandibular joint (TMJ) experience similar incidence of cartilage ailments, the knee orthopedics field has greater funding and more effective end-stage treatment options. Translational research has resulted in the development of tissue-engineered products for knee cartilage repair, but the same is not true for TMJ cartilages. Here, we examine the anatomy and pathology of the joints, compare current treatments and products for cartilage afflictions, and explore ways to accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…However, the TMJ is one of the least understood joints of our body and performs activities such as communicating, eating, and smiling [ 3 ]. Recently, Bielajew et al reported that the knee and the TMJ have similar osteoarthritis incidence, but the latter lacks research and grant funding, cell-based therapies, and specialist doctors in the field [ 4 ]. Moreover, even one year after the end of lockdown induced by the COVID-19 pandemic, dental consultations were reduced, leading to further aggravation of TMJ dysfunctions (TMD) and bruxism [ 5 ].…”
Section: Why Is There a Need To Investigate Tmj Disc Substitutes?mentioning
confidence: 99%
“…However, the TMJ is one of the least understood joints of our body and performs activities such as communicating, eating, and smiling [ 3 ]. Recently, Bielajew et al reported that the knee and the TMJ have similar osteoarthritis incidence, but the latter lacks research and grant funding, cell-based therapies, and specialist doctors in the field [ 4 ]. Moreover, even one year after the end of lockdown induced by the COVID-19 pandemic, dental consultations were reduced, leading to further aggravation of TMJ dysfunctions (TMD) and bruxism [ 5 ].…”
Section: Why Is There a Need To Investigate Tmj Disc Substitutes?mentioning
confidence: 99%
“…Although there are many differences, the two joints manifest similar pathologies and disorders (17). [55] The prevalence of OA is similar, with approximately 14% of USA adults suffering from knee OA, compared with 8%-16% of the population suffering from TMJ OA (24,25). [56,57] Despite a similar incidence of OA, the knee joint has a sixfold higher number of related articles and a 2,000-fold higher total joint replacement frequency compared to the TMJ.…”
Section: Materials For Cartilage Reconstructionmentioning
confidence: 99%
“…At the same time, the field of knee orthopedics has more funding and more effective end-stage treatment options (17). [55] Bearing compressive, tensile and shear loads during joint movement, condylar cartilage is one of the most indispensable structures to maintain function of TMJ. TMJ OA leads to progressive degeneration of this important structure (50), so regeneration of the condylar cartilage is significant.…”
Section: Materials For Cartilage Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TMJ disc separates an upper and lower joint capsule and acts to distribute shear and compressive forces throughout the range of jaw movements [2]. Musculoskeletal conditions of the TMJ complex are classified by a wide range of symptoms including functional limitations and orofacial pain, which may be myogenous or arthrogenous [3][4][5]. Pain in the TMJ is prevalent, effecting approximately 10% of the population over the age of 18 [6].…”
Section: Introductionmentioning
confidence: 99%